2019
DOI: 10.3168/jds.2019-16436
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various doses of an exogenous acid protease on the fermentation and nutritive value of corn silage

Abstract: The objective of this experiment was to evaluate the effects of treating whole-plant corn at harvest with various doses of an exogenous acidic protease on fermentation and changes in nutritive value after a short period (45 d) of ensiling. Whole-plant corn (37% dry matter) was chopped and treated with 0, 20, 200, 1,000, or 2,000 mg of protease/kg of wet forage. Forages (~500 g) were packed in bag silos and ensiled at 22 to 23°C for 45 d. Data were analyzed as a 5 × 2 factorial arrangement of treatments with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The digestive enzyme could catalyze and decompose feedstuff into molecules for animals to use, for example, amylase could decompose the starch into glucose and further enhance the ruminants’ starch digestibility [ 7 ]. The exogenous protease could alert the amino acid composition and improve the starch digestibility of corn silage [ 8 ]. Bacteria, enzymes, and the VFA, MCP, pH, and NH 3 -N, are closely related and jointly assist in completing the rumen digestive function.…”
Section: Introductionmentioning
confidence: 99%
“…The digestive enzyme could catalyze and decompose feedstuff into molecules for animals to use, for example, amylase could decompose the starch into glucose and further enhance the ruminants’ starch digestibility [ 7 ]. The exogenous protease could alert the amino acid composition and improve the starch digestibility of corn silage [ 8 ]. Bacteria, enzymes, and the VFA, MCP, pH, and NH 3 -N, are closely related and jointly assist in completing the rumen digestive function.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, Colombatto and Beauchemin (2009) , when testing an exogenous protease have reported greater IVDMD of several substrates including a TMR after 22 h of incubation. Similarly, studies evaluating the effects of proteases as silage additives have reported greater IVSD when compared with control ( Ferraretto et al, 2015a ; Ferraretto et al, 2015b ; Der Bedrosian and Kung Jr, 2019 ).…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, exogenous proteases or blends of enzymes containing proteases have been evaluated as feed additives in total mixed ration (TMR) of both dairy and beef cows; however, studies have reported greater ( Eun and Beauchemin, 2005 ; Gado et al, 2009 ) or no effect ( Vera et al, 2012 ; Meschiatti et al, 2019 ) on animal performance when compared with control. Exogenous proteases have also been used as additives in high-moisture and whole-plant corn silage and results showed greater corn starch digestibility when compared to control due to the breakdown of the protein matrix surrounding the starch granules ( Young et al, 2012 ; Kung Jr et al, 2014 ; Ferraretto et al, 2015a ; Der Bedrosian and Kung Jr, 2019 ). Despite these studies, there is limited literature available on the effects of the direct addition of endo-acting α-amylases and proteases on mature corn grain on in vitro dry matter and starch digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of mechanical processing and storage on the AA profile of WPMS are often overlooked in silage research. Der Bedrosian and Kung [52] observed that ensiling had no effect on the concentrations of total NEAA and total AA. However, ensiling caused a slight decrease in total EAA [52].…”
Section: Silage Aa Compositionmentioning
confidence: 97%
“…Der Bedrosian and Kung [52] observed that ensiling had no effect on the concentrations of total NEAA and total AA. However, ensiling caused a slight decrease in total EAA [52]. Changes in concentrations of the total AA have been reported when forages are ensiled [53].…”
Section: Silage Aa Compositionmentioning
confidence: 97%